Optimization of TSV interconnects and BEOL layers under annealing process through fracture evaluation. Issue 7 (9th February 2020) - Qin, F.; Zhang, M.; Dai, Y.; Chen, P.; An, T.; He, H.; Zhang, H.; Zheng, J.
Abstract: Through silicon via (TSV) is a crucial interconnection structure in 3‐D integrated circuits. However, protrusion and intrusion of TSV‐Cu caused by annealing could lead to cracking and failure of back‐end‐of‐line (BEOL) layers and TSV interconnects due to mismatch of coefficient of thermal expansion. In this paper, optimizations of TSV interconnects and BEOL layers under annealing process are investigated based on fracture evaluation. Influences of geometrical factors including the TSV geometry dimension, the distance between TSV and BEOL layers, and pitch size of Cu via on energy release rate and J ‐integral are studied for TSV interconnects and BEOL layers with cracks. Effect of material properties for low k dielectrics on interfacial fracture of BEOL layers and TSV interconnects is also given. Optimized geometrical factors and optimized material properties of low k dielectrics are presented in this paper. Fracture‐based method sheds a light on emerging electronic packaging optimization.